Rhynchophylline alleviates cognitive deficits in multiple transgenic mouse models of Alzheimer’s disease via modulating neuropathology and gut microbiota - Zhong Mei; Xu Qing-qing; Huang Ming-qing; Zhan Ruo-ting; Huang Xiao-qi; Yang Wen; Lin Zhi-xiu; Xian Yan-fang (Acta Pharmacologica Sinica, 2025)
Amyloid-beta (Aβ) aggregation, phosphorylated tau accumulation and neuroinflammation are considered as three hallmarks of Alzheimer’s disease (AD). Rhynchophylline (RN), the major alkaloid of a Chinese medicinal plant Uncaria rhynchophylla, has been shown to possess potent anti-AD effects. This study explored the effects of RN on Aβ pathology, tauopathy, and neuroinflammation using three AD mouse models, including TgCRND8, 3×Tg-AD, and 5×FAD, with RN treatment lasting for 4, 6, and 6 months, respectively, followed by behavioral tests and biological assays. In addition, BV2 cells were employed to further evaluate the biological effects of RN. RN treatment improved cognitive functions by reducing anxiety-like behaviors, enhancing recognition ability, and ameliorating learning impairments. It modulated Aβ processing through reducing the Aβ-producing enzyme activities and enhancing degradation enzyme activities, thereby diminishing Aβ accumulation. RN also decreased hyperphosphorylated tau proteins at Thr181, Thr205, Ser396, and Ser404 sites. Moreover, RN diminished neuroinflammation by reducing microglia and astrocyte activation and lowering the release of inflammatory cytokines. Furthermore, RN treatment could restore gut microbiota dysbiosis in 5×FAD mice. In BV2 cells, knockdown of p53, HDAC2, and Galectin-3 markedly enhanced the anti-inflammatory effects of RN. Overall, the anti-AD properties of RN were attributed to its regulation of multiple biological pathways, including regulation of the p53/PINK1 signaling pathway, inhibition of the HDAC2/AMPK signaling pathway, suppression of the Galectin-3/C/EBPβ/AEP signaling pathway, and modulation of gut microflora dysbiosis. This pioneering study unambiguously revealed the effects of RN on cognitive impairments, APP processing, tauopathy, and neuroinflammation in different transgenic mouse models with differing AD burdens, highlighting its potential as an anti-AD therapeutic agent and enhancing the scientific basis for its clinical use in treating AD.